General Review of Legal Relations and Responsibility of Carriers in Sea Transportation - Maulinasari, Leyla (Faculty of Law, Universitas Negeri Semarang, 2022)
The issues raised in this journal are about how the responsibility of the carrier in the implementation of the transport of goods through water transport, especially sea transportation. This is intended to determine the role that must be done by the carrier in the transportation process in order to achieve the maximum goal. This study also describes how the legal relationship between the carrier and the user of the freight service so that both parties can bind each other in the process of transportation so that there is no loss or other undesirable things. It can be deduced that in a transport of goods carried by the carrier through water transport is the responsibility of the carrier if someday there is a loss or bad things during the transportation process. Therefore, it is necessary full sense of responsibility from the carrier and also the legal relationship between the carrier and the user of the transport service to ensure the safety of the goods he was transporting until the goods arrived at the destination. There should also be a loss if an accident is found on the goods being transported.